Odpowiedzi

2010-04-13T19:53:58+02:00
-5t + t - 6 - 7t + 8t + 2 + 2t dla t = -3,2
-t-4 = -(-3,2) -4 = 3,2-4 = -0,8

-7x + 6x + 3x - 2y + x - 3y dla x = -2_3(dwie trzecie)i y = 4_7(cztery siódme)
3x -5y = 3 * (-⅔) -5* (⁴/₇) = -2 - ²⁰/₇ = -2 - 2 ⁶/₇ = -4 ⁶/₇
2 5 2
2010-04-13T19:55:02+02:00
-5t + t - 6 - 7t + 8t + 2 + 2t dla t = -3,2
-t-4
-3,2 - 4 = - 7,2


-7x + 6x + 3x - 2y + x - 3y dla x = -2_3(dwie trzecie)i y = 4_7(cztery siódme)

3x - 5y
-2/3 * 3 - 5* 4/7 = -2 - 2 i 6/7 = - 4 i 6/7
2010-04-13T19:55:53+02:00
-5t+t-6-7t+8t+2+2t = -t-4 dla t = -3,2
-t-4 = -3,2 - 4 = -7,2

-7x + 6x + 3x - 2y + x - 3y = 3x - 5y
dla x = -2_3(dwie trzecie)i y = 4_7(cztery siódme)
3x - 5y = -2 - 2 i 6/7 = - 4 i 6/7 (6/7 = szesc siodmych)